Roomscape Women Writers in the British Museum from George Eliot to Virginia Woolf - Bernstein, Susan David (Edinburgh University Press, 2022)
Examines the Reading Room of the British Museum as a space of imaginative and historically generative potential in relation to the emergence of modern women writers in Victorian and early twentieth-century LondonGBS_insertPreviewButtonPopup(['ISBN:9780748640652','ISBN:9780748681617']);'Roomscape deserves to find a readership, for its original pursuit of a rich topic and the possibilities it suggests for further study.' - Matthew Ingleby, TLS'By drawing women back towards the foci of 19th-century intellectual life, Bernstein has done library history a great service.' - Colin Higgins, Librarian, St Catharine's College, Cambridge, THEDrawing on archival materials around this national library reading room, Roomscape is the first study that integrates documentary, theoretical, historical, and literary sources to examine the significance of this public interior space for women writers and their treatment of reading and writing spaces in literary texts. This book challenges an assessment of the Reading Room of the British Museum as a bastion of class and gender privilege, an image firmly established by Virginia Woolf's 1929 A Room of One's Own and the legions of feminist scholarship that upholds this spatial conceit.Susan David Bernstein argues not only that the British Museum Reading Room facilitated various practices of women's literary traditions, she also questions the overdetermined value of privacy and autonomy in constructions of female authorship, a principle generated from Woolf's feminist manifesto. Rather than viewing reading and writing as solitary, individual events, Roomscape considers the meaning of exteriority and the public and social and gendered dimensions of literary production.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 06. Mrz 2022)
Keywords: Literary Studies; LITERARY CRITICISM / Women Authors; Authorship; English literature -- Women authors -- History and criticism; Reading rooms -- England -- London -- History; Women authors -- Societies, etc